1988
DOI: 10.1177/154193128803200303
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Older Drivers: A Study of their Over-Involvement Ratio

Abstract: An analysis of reports of 660 two-car collisions from the records of an insurance company showed that car drivers of 60 years old and older are more apt to be considered liable in an accident than younger drivers. A comparison of accidents for which older drivers (60 yrs. and over) are responsible with accidents for which younger drivers (30–39 yrs.) are responsible showed that the former have problems of perception and decision making and that the latter have problems with speed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…If a group has a ratio of at-fault accidents to not-at-fault accidents greater than one, then the group is involved in more than its expected share of two-vehicle accidents. Accident responsibility ratio increases at an accelerating rate after the age of sixty-five (Cooper, 1989(Cooper, , 1990Janke, 1991;Stamatiadis & Deacon, 1995;Verhaegen, Toebat, & Delbeke, 1988). The proportion of right of way (ROW) violations to total traffic convictions by age also follows a similar rising curve (Cooper, 1990).…”
Section: Introductionmentioning
confidence: 70%
“…If a group has a ratio of at-fault accidents to not-at-fault accidents greater than one, then the group is involved in more than its expected share of two-vehicle accidents. Accident responsibility ratio increases at an accelerating rate after the age of sixty-five (Cooper, 1989(Cooper, , 1990Janke, 1991;Stamatiadis & Deacon, 1995;Verhaegen, Toebat, & Delbeke, 1988). The proportion of right of way (ROW) violations to total traffic convictions by age also follows a similar rising curve (Cooper, 1990).…”
Section: Introductionmentioning
confidence: 70%
“…Drivers must decide whether or not to drive after consuming alcohol, if they should pass another vehicle, or obey the posted speed limits. Whereas Verhaegen et al (1988) suggested that poor decision making is a major contributing factor in accidents involving elderly drivers, younger drivers may display poor judgment through their increased risk-taking behaviors such as speeding. Whereas tests of cognitive processing speed and psychomotor skills may help identify those that are unable to safely operate a vehicle, these tests may not be able to identify those that simply choose not to follow safe driving procedures.…”
Section: Future Directionsmentioning
confidence: 96%
“…Failure to yield is likely indicative of a failure to attend to the situation (e.g., traffic signs, other vehicles), rather than poor visual acuity. Verhaegen et al (1988) found that the types of accidents in which drivers were at fault differed by age group. That is, younger drivers (30-39 years) were more likely to be involved in accidents caused by their risk-taking behavior (i.e., driving at excessive speeds, passing over the centerline, and following too closely), whereas older drivers were more likely to be involved in accidents caused by poor decision making (e.g., turning into traffic with insufficient gap).…”
Section: Accident Causesmentioning
confidence: 97%
See 1 more Smart Citation
“…Age-related increases in both right of way (ROW) violations and accident responsibility (Cooper, 1990;Janke, 1991;Stamatiadis & Deacon, 1995;Verhaegen, Toebat, & Delbeke, 1988) may result from failure to detect other vehicles in the right-of-way. Accident characteristics support this hypothesis.…”
Section: Introductionmentioning
confidence: 99%